2017
DOI: 10.1176/appi.ps.201600304
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clinical High-Risk State a Valid Concept? Retrospective Examination in a First-Episode Psychosis Sample

Abstract: Most consenting patients with an FEP had experienced previous signs and symptoms consistent with a CHR state prior to the onset of threshold-level psychotic symptoms, although a substantial minority had not. This finding validates the viability of the CHR construct as a potential target for early case identification and preventive and therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 26 publications
2
68
1
1
Order By: Relevance
“…As well as early intervention for FEP, a new approach has emerged over the past two decades, based on the ability to identify help-seeking individuals displaying clinical features of an "At Risk Mental State," also described as "Ultra High-Risk" and "Clinical High-Risk for Psychosis (CHR-P)" (Fusar-Poli et al, 2012;Fusar-Poli, 2017;Yung et al, 1996;Yung, Phillips, Yuen, & McGorry, 2004). Of relevance for this study, recent evidence confirmed that most FEP cases are preceded by CHR-P features (Shah et al, 2017). Help-seeking behaviour (Falkenberg et al, 2015) and functional deterioration are usual.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…As well as early intervention for FEP, a new approach has emerged over the past two decades, based on the ability to identify help-seeking individuals displaying clinical features of an "At Risk Mental State," also described as "Ultra High-Risk" and "Clinical High-Risk for Psychosis (CHR-P)" (Fusar-Poli et al, 2012;Fusar-Poli, 2017;Yung et al, 1996;Yung, Phillips, Yuen, & McGorry, 2004). Of relevance for this study, recent evidence confirmed that most FEP cases are preceded by CHR-P features (Shah et al, 2017). Help-seeking behaviour (Falkenberg et al, 2015) and functional deterioration are usual.…”
mentioning
confidence: 78%
“…Since most cases of psychosis are preceded by CHR-P (Shah et al, 2017) and 36% of people with CHR-P develop FEP after 3 years (Fusar-Poli et al, 2012), number of new CHR-P cases were estimated as at least three times higher than number of FEPs. For this paper, we therefore estimated annual CHR-P incidence as 200/100 000 of the 15-34 population although also applied a more conservative annual incidence of 150/100 000.…”
Section: -34 Year Oldsmentioning
confidence: 99%
“…Within the first 3 months of entry into PEPP, patients were evaluated with the Topography of Psychotic Episode (TOPE) , a retrospective assessment of 27 potential early signs and symptoms of psychosis. The TOPE is part of the Circumstances of Onset and Relapse Schedule (CORS), which determines pathways to care through detailed interviews with the patient and, when available, his or her relative(s), and review of all health and educational records.…”
Section: Methodsmentioning
confidence: 99%
“…Although the results of these studies have been inconsistent, previous efforts comparing patients entering FEP services de novo (vs. those who entered after receiving interventions during the CHR phase) presume that the former group would have invariably experienced STPS. Yet recent reports indicate that only 46–68% of FEP patients report STPS before their psychosis and that these symptom trajectories predict differential clinical and functional outcomes over time .…”
Section: Introductionmentioning
confidence: 99%
“…This means that specialised UHR services that focus exclusively on early psychotic symptoms may not capture all cases who transition to psychosis as alternative pathways leading to a psychotic disorder have emerged. For instance, they have been shown to emerge following a period of non-psychotic at-risk states,18 with approximately one-third of patients with FEP not experiencing subthreshold psychotic symptoms 19. This suggests that the wider enhanced primary care youth mental health model of headspace is likely to capture a fuller range of pathways and be more inclusive 20.…”
Section: Transition and Its Limitationsmentioning
confidence: 99%